Tujuan Pendidikan dalam Perspektif Al-Qur'an - As'aril Muhajir (AL-TAHRIR, 2011)
Al-Quran as a guidance to life for Muslims does not give details about the ins and outs of education. However, there are several terms related to educational issues in this holy books. This article tries to get a complete sketch of the nature and purpose of education in Islam by discussing the meaning of these terms according to the language experts and education thinkers, so that the opinions of mutual support among them will be used as the basis to draw the conclusion. This paper comes to the conclusion that the terms tarbiyah, ta ’lim, ta ’dib, tazkiyah and tahdhib give the message about the nature of education and its aims. The purpose of education in the perspective of the Qur’an is focused in three points. First, to achieve complete human being in the pillars of his life. Second, to build a comprehensive human dimension of religion, culture, and science. Third, to make human beings resposible of their function as servants of God and inheritors of the Prophet. The very nature of some of these goals is to achieve a true Muslim characterized with the notion of rah}matan li al-’a> lami>n. Thus, the purpose of Islamic education in the Qur’an is not merely the transfer of knowledge, but is also the the transfer process of value. This purpose is also related to effort to establish the h}abl min Alla>h, h}abl min al-na>s, and h}abl min al- ’a> lam, that is the good relation with God, mankind, and the nature.